Frontiers: ChatGPT Referrals to E-Commerce Websites: How Do LLMs Compare Against Traditional Channels? - Kaiser, Maximilian; Schulze, Christian (Marketing Science, 2026)
This is a descriptive study reporting financial and engagement metrics for 973 e-commerce websites, comparing organic large language model traffic (oLLM) with traditional digital channels.